The systems approach to development of integrated management system for chemical enterprises - V. F. Kornyushko; E. G. Khomutova; E. V. Guschin (Тонкие химические технологии)
On the base of systems approach the selection task of integrated management system structure was analyzed. Integrated management system on the chemical enterprises includes as a rule several systems: quality management system as a base system, environmental protection system, professional safety and employment protection system, GMP system, etc. It was suggested the solve method of structure selection task and business-processes distribution among enterprise departments